2022
DOI: 10.1097/ccm.0000000000005503
|View full text |Cite
|
Sign up to set email alerts
|

The β1-Adrenergic Receptor Contributes to Sepsis-Induced Immunosuppression Through Modulation of Regulatory T-Cell Inhibitory Function*

Abstract: Although cardiovascular benefits of β 1 -adrenergic receptor blockade have been described in sepsis, little is known about its impact on the adaptive immune response, specifically CD4 T cells. Herein, we study the effects of β 1 -adrenergic receptor modulation on CD4 T-cell function in a murine model of sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…Basic differences in pathophysiology-hypothermia/ bradycardia versus fever/tachycardia-and differences in inflammatory gene expression have been mentioned. Indeed, the CLP-induced bradycardia documented by Durand et al (5) belies the statement that the model "depicts all hemodynamic … characteristics of a typical mid-grade sepsis. " Further, mice are more resistant to infection than humans.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…Basic differences in pathophysiology-hypothermia/ bradycardia versus fever/tachycardia-and differences in inflammatory gene expression have been mentioned. Indeed, the CLP-induced bradycardia documented by Durand et al (5) belies the statement that the model "depicts all hemodynamic … characteristics of a typical mid-grade sepsis. " Further, mice are more resistant to infection than humans.…”
mentioning
confidence: 88%
“…The findings of Durand et al (5) are also unique in their focus on β1ARs. Previous studies suggest that adrenergic effects on leukocytes to promote immunosuppression are β2AR-mediated (9).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…The bene cial effects of Esmolol in septic shock were previously considered due to its hemodynamic effects [9]. However, recent evidence showed that the bene cial effects of Esmolol in septic shock were also associated with immunomodulation [10,11]. Whereas, how Esmolol in uencing immune response in septic shock and the optimal dose are unclear.…”
Section: Introductionmentioning
confidence: 99%